White-tailed eagle (Haliaeetus albicilla) and great cormorant (Phalacrocorax carbo) nestlings as spatial sentinels of Baltic acidic sulphate soil associated metal contamination - Vainio Riikka Katariina; Eulaers Igor; Laaksonen Toni; Vasko Ville; Jormalainen Veijo (Elsevier BV, 2022)
Sulphate soils, characterised by low pH conditions, are found worldwide, and are potentially large sources of metal contamination, often exceeding industrial emissions. Metal leaching from sulphate soils has been shown to be harmful to aquatic organisms, but the cascading effect on exposure in apex avian predators has not been studied earlier. With the present study we aimed at evaluating the potential of white-tailed eagle (Haliaeetus albicilla) and great cormorant (Phalacrocorax carbo) nestlings, collected from nests located either in sulphate soil or control areas, for monitoring spatial contaminant trends of metals typically associated with sulphate soils.
In blood of white-tailed eagles, the concentrations of aluminium and cobalt were significantly higher in sulphate soil areas. In blood of great cormorants, the concentrations of copper and manganese were so, while the concentration of zinc was found to be lower. Also, we observed an interaction between the latitude and soil type in cobalt and lithium concentrations of great cormorants, showing that concentrations in the sulphate soil associated nestlings rose more steeply towards the north than in the control group. Latitudinal trends of higher concentrations in the south were found in cadmium, manganese, and copper of white-tailed eagle nestlings, while thallium of white-tailed eagle nestlings, and thallium and zinc of great cormorant nestlings showed a latitudinal trend of higher concentrations in the north. Concentrations of several metals correlated positively within a species indicating covariation in metal exposure. Generally, the metal concentrations in both species were similar to levels reported to be below toxicity thresholds in other species. These results indicate, that white-tailed eagle and great cormorant nestling metal burdens may indicate environmental contamination from acidic sulphate soil runoff, and that they may act as indicators of latitudinal gradient identifying different contamination sources.